Fabrication of silica ceramic membrane via sol-gel dip-coating method at different nitric acid amount - Kahlib, N. A.Z.; Mohd Daud, Farah Diana; Mel, Maizirwan; Nor Hairin, Assayidatul Laila; Ahmad Azhar, Ahmad Zahirani; Hassan, Noor Azlina (Institute of Physics Publishing, 2018)
Fabrication of silica ceramics via the sol-gel method has offered more advantages over other methods in the fabrication of ceramic membrane, such as simple operation, high purity homogeneous, well defined-structure and complex shapes of end products. This work presents the fabrication of silica ceramic membrane via sol-gel dip-coating methods by varying nitric acid amount. The nitric acid plays an important role as catalyst in fabrication reaction which involved hydrolysis and condensation process. The tubular ceramic support, used as the substrate, was dipped into the sol of Tetrethylorthosilicate (TEOS), distilled water and ethanol with the addition of nitric acid. The fabricated silica membrane was then characterized by (Field Emission Scanning Electron Microscope) FESEM and (Fourier transform infrared spectroscopy) FTIR to determine structural and chemical properties at different amount of acids. From the XRD analysis, the fabricated silica ceramic membrane showed the existence of silicate hydrate in the final product. FESEM images indicated that the silica ceramic membrane has been deposited on the tubular ceramic support as a substrate and penetrate into the pore walls. The intensity peak of FTIR decreased with increasing of amount of acids. Hence, the 8 ml of acid has demonstrated the appropriate amount of catalyst in fabricating good physical and chemical characteristic of silica ceramic membrane.